Cardiopulmonary changes in Rheumatoid arthritis - Nigam, Pradeep; Baghel P.K., P K; Jain, MK; Kushawha, Prashant (International Journal of Medical Research and Review, 2014)
Introduction: Rheumatoid arthritis should be viewed as a multisystem disease affecting multiple organs. Vigilance for lung and cardiac involvement is necessary among rheumatologists and patients. Despite the absence of effective treatment for advanced respiratory and cardiovascular disease, it is possible that therapeutic intervention at an early stage may be beneficial. Keeping in view the above mentioned facts, we have undertaken this study to see the various cardiac and pulmonary changes associated with rheumatoid arthritis and, their age and sex wise distribution in study population. Objective: To study prevalence and severity of cardiovascular and pulmonary changes in patients of rheumatoid arthritis in accordance to age and sex. Method: All patients fulfilling 1987, revised criteria for diagnosis of rheumatoid arthritis, proposed by American College of Rheumatology were selected without any bias for age, sex, duration, severity of disease. Result: Female to male ratio was 2.6: 1 with hypertension as most common co-morbid disease. Anti-cyclic citrullinated peptide was more specific than rheumatoid factor. 40.5% cases had abnormal pulmonary function test results in the form of restrictive and/or obstructive abnormality. 35.7% had abnormal echocardiography with valvular lesions, pericardial effusion and left ventricular dysfunction in decreasing order. Mitral valve was involved in 87.5% of total valvular involvement. Conclusion: Cardiopulmonary involvement was restrictive pattern of lung involvement along with mitral valve lesions, pericardial effusion and left ventricular dysfunction. Anti-cyclic citrullinated peptide was more specific than rheumatoid factor.